Diversidade dos metazoários parasitos de peixes carnívoros: Serrasalmus altispinis (Merckx, Jégu e Santos, 2000); Rhaphiodon vulpinus (Spix & Spix, 1829), e Acestrorhynchus falcatus (Bloch, 1794) de lagos de Várzea da Amazônia. - Murrieta Morey, Germán Augusto (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
This work describes the parasitic fauna of Serrasalmus altispinis caught in Central Amazonia floodplain lakes and its use as a bioindicator of environmental quality. All registered parasite species are first records for this fish species. Additional information to the original descriptions of the parasite species already described were added. The studied lakes were: Baixio, Preto, São Tomé, Ananá, Araçá and Maracá, located between the cities of Manaus and Coari in Central Amazonia, in a stretch of approximately 400 km. Sixty S. altispinis were collected and examined during four field trips in the months of March, June, September, and December 2013. Fish averaged standard length was 13.3 ± 3.6 cm and 60.3 ± 35, 9 g of total weight. The relative condition factor was 1.14 ± 0.95. One thousand one hundred and twenty two (1122) parasites belonging to three phyllum and six different taxonomic groups were collected and identified: Phylum Platyhelminthes: Monogenoidea (818) and Digenea (22); Phylum Nematoda (70), and Phylum Arthropoda: Copepoda (196), Branchiura (01) and Isopoda (15). Ecological descriptors such as the Margalef and Simpson diversity indexes showed high diversity in the lakes, except for Lake Baixio, which presented values that considered it as a lake of medium diversity. However, when the calculation of diversity indices was applied only to endoparasites, they showed a different picture: the low values in the ecological descriptors considered the studied lakes as places of low diversity. All lakes had more ectoparasites than endoparasites. The species Anacanthorus jegui, A. peryphallus, A. sciponophallus, Enallothecium aegidatum, Clinostomum marginatum, Procamallanus (Spirocamallanus) inopinatus, Anisakis sp and Amplexibranchius bryconis presented IndVal significant greater than 70% (p <0.05) being considered as characteristic species in the floodplain lakes studied. The great diversity of parasite species that use S. altispinis as host indicates the important role that this fish species has for the maintenance of biodiversity in floodplain lakes of Brazilian Central Amazonia.
Keywords: Serrasalmus altispinis; Rhaphiodon vulpinus; Acestrorhynchus falcatus; Parasitas de peixes carnívoros